First Very Long Baseline Interferometry Detections at 870 μm - Raymond, Alexander W. (Institute of Physics Publishing, 2025)
The first very long baseline interferometry (VLBI) detections at 870 μm wavelength (345 GHz frequency) are reported, achieving the highest diffraction-limited angular resolution yet obtained from the surface of the Earth and the highest-frequency example of the VLBI technique to date. These include strong detections for multiple sources observed on intercontinental baselines between telescopes in Chile, Hawaii, and Spain, obtained during observations in 2018 October. The longest-baseline detections approach 11 Gλ, corresponding to an angular resolution, or fringe spacing, of 19 μas. The Allan deviation of the visibility phase at 870 μm is comparable to that at 1.3 mm on the relevant integration timescales between 2 and 100 s. The detections confirm that the sensitivity and signal chain stability of stations in the Event Horizon Telescope (EHT) array are suitable for VLBI observations at 870 μm. Operation at this short wavelength, combined with anticipated enhancements of the EHT, will lead to a unique high angular resolution instrument for black hole studies, capable of resolving the event horizons of supermassive black holes in both space and time.